A (New) Old Iranian Etymology for Biblical Aramaic ‮אֲדַרְגָּזַר‬‎ - Noonan, Benjamin J. (Aramaic studies, 2018)
Despite the many advances that have taken place in our understanding of the Hebrew Bible’s Old Iranian terminology, the donor terms of several words have remained elusive. Among them is Biblical Aramaic ‮אֲדַרְגָּזַר‬‎ (Dan. 3:2–3). Proposed Old Iranian etymologies for this word suffer from various phonological and semantic difficulties, rendering them unlikely. This paper proposes that Biblical Aramaic ‮אֲדַרְגָּזַר‬‎ is best derived from *ādrangāžara- ‘announcer of financial obligation’, a compound of *ādranga- ‘financial obligation’ and *āžara- ‘announcer’. A derivation from Old Iranian *ādrangāžara- adequately explains the form of Biblical Aramaic ‮אֲדַרְגָּזַר‬‎. Furthermore, this etymology also suits the context well in that ‮אֲדַרְגָּזַר‬‎ occurs just prior to ‮גְּדָבַר‬‎ ‘treasurer’ and therefore falls logically within the progression from political administration to finances to law evident in the lists of Nebuchadnezzar’s officials (Dan. 3:2–3).